Functional Roles of JNK and p38 MAPK Signaling in Nasopharyngeal Carcinoma - Pua, Lesley Jia Wei; Mai, Chun Wai; Chung, Felicia Fei Lei *; Khoo, Alan Soo Beng; Leong, Chee Onn; Lim, Wei Meng; Hii, Ling Wei (MDPI, 2022)
c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) family members integrate signals that affect proliferation, differentiation, survival, and migration in a cell context- and cell type-specific way. JNK and p38 MAPK activities are found upregulated in nasopharyngeal carcinoma (NPC). Studies have shown that activation of JNK and p38 MAPK signaling can promote NPC oncogenesis by mechanisms within the cancer cells and interactions with the tumor microenvironment. They regulate multiple transcription activities and contribute to tumor-promoting processes, ranging from cell proliferation to apoptosis, inflammation, metastasis, and angiogenesis. Current literature suggests that JNK and p38 MAPK activation may exert pro-tumorigenic functions in NPC, though the underlying mechanisms are not well documented and have yet to be fully explored. Here, we aim to provide a narrative review of JNK and p38 MAPK pathways in human cancers with a primary focus on NPC. We also discuss the potential therapeutic agents that could be used to target JNK and p38 MAPK signaling in NPC, along with perspectives for future works. We aim to inspire future studies further delineating JNK and p38 MAPK signaling in NPC oncogenesis which might offer important insights for better strategies in diagnosis, prognosis, and treatment decision-making in NPC patients.